Kebijakan Afirmatif di Malaysia: Analisis Idiosinkretis Penolakan Mahathir Mohamad untuk Meratifikasi ICERD - Karisma, Dela; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
In November 2018 Mahathir Mohamad, who re-assumed the position of Prime Ministerof Malaysia stated that Malaysia would not ratify ICERD. It is considered by some to be asetback for the struggle of equalization of racial rights in Malaysia. Previous research on racialdiscrimination in Malaysia focused mostly on the human rights side and the roots ofdiscrimination itself without specifically addressing the issue of ICERD. This study will analyzethe rationale behind Malaysia's refusal to ratify ICERD using an idiosyncratic theory.Researcher place the level of analysis at the individual level, by examining Mahathir Mohamad.By analyzing elements of Mahathir Mohamad’s leadership style, the researcher argues that thestrong driving factor behind Malaysia's refusal to ratify ICERD is an element of Mahathir'sexperience and interest in politics as a person who was predominantly Malay-chauvinist becauseof his Malay-centric ideas.